Dark water - Nakata, Hideo, 1961-; Kuroki, Hitomi, 1960-; Kanno, Rio, 1993-; Oguchi, Mirei; Kawai, Kenji, 1957-; A.D.V. Films (Firm) ([United States] : ADV Films, 2005)
Yoshimi Matsubara fights to gain legal custody of her five year-old daughter Ikuko while the two live together in a dark, sullen and musty apartment building. Already insecure and uncertain about her future with her daughter, Yoshimi is haunted by murky water dripping through the ceiling and walls, and by the almost taunting appearances of a small red bag that once belonged to a girl who had mysteriously disappeared two years prior. Though she desperately struggles to find the strength within herself for Ikuko's sake, her horror intensifies as she comes closer to discovering the connection between these events, and is completely unprepared for the truth that lies ahead.
Title from container.
Originally released as a motion picture in 2001.
Based on the book by Koji Suzuki.
Special features: Original Japanese trailer.
Cinematographer, Junichiro Hayashi ; editor, Nobuyuki Takahashi ; music, Kenji Kawai.
Hitomi Kuroki, Rio Kanno, Mirei Oguchi, Asami Mizukawa.
Keywords: Apartment houses -- Juvenile drama; Custody of children -- Juvenile drama; Mothers and daughters -- Juvenile drama; DVD-Video discs; Video recordings; Drama; Feature films; Horror films